2015
DOI: 10.1152/ajpgi.00226.2015
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol exposure affects pancreatic acinar mitochondrial thiamin pyrophosphate uptake: studies with mouse 266-6 cell line and primary cells

Abstract: Thiamin is essential for normal metabolic activity of all mammalian cells, including those of the pancreas. Cells obtain thiamin from their surroundings and enzymatically convert it into thiamin pyrophosphate (TPP) in the cytoplasm; TPP is then taken up by mitochondria via a specific carrier the mitochondrial TPP transporter (MTPPT; product of the SLC25A19 gene). Chronic alcohol exposure negatively impacts the health of pancreatic acinar cells (PAC), but its effect on physiological/molecular parameters of MTPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 45 publications
3
22
0
1
Order By: Relevance
“…266-6 cells retain a partially differentiated phenotype and express several digestive-enzymes 20 . They respond to carbachol and CCK and have been used to investigate the physiology and pathology of the pancreas 21 . We observed that high dose of LLOMe treatment leads to significant cell death in 266-6 cell line through necrosis as indicated by increased LDH release (Supplementary figure-7).…”
Section: Resultsmentioning
confidence: 99%
“…266-6 cells retain a partially differentiated phenotype and express several digestive-enzymes 20 . They respond to carbachol and CCK and have been used to investigate the physiology and pathology of the pancreas 21 . We observed that high dose of LLOMe treatment leads to significant cell death in 266-6 cell line through necrosis as indicated by increased LDH release (Supplementary figure-7).…”
Section: Resultsmentioning
confidence: 99%
“…Control animals received regular (no nicotine) water. After 4 weeks the mice were euthanized and the pancreas was removed and primary PAC were isolated by a collagenase type-V (Sigma, St. Louis, MO) digestion method as described previously [ 36 38 ]. Freshly isolated PAC were used for uptake analysis on the day of isolation with a portion stored at −80°C for protein, mRNA expression and firefly luciferase analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Pair feeding of transgenic mice carrying the SLC25A19 promoter with thiamin-DEF and -OS diets. We pair fed (for 6 wk) transgenic mice recently generated and characterized in our laboratory (38) that carry the human SLC25A19 gene promoter [i.e., 1,080 bp (Ϫ860 to ϩ220) fragment fused with firefly luciferase reporter genes], with a thiamin-DEF or -OS diet. These two diets were identical (AIN-93G purified thiamin-deficient rodent diet; Dyets, Bethlehem, PA), but the latter one contained 6 mg/kg of added thiamin (26,32) (animals were fed this thiamin deficient diet for the specified period to develop thiamin deficiency).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, we have cloned and characterized the SLC25A19 promoter and have identified an important role for the nuclear factor NF-Y in driving its basal activity (24). Furthermore, we have investigated the effect of certain environmental/external factors (specifically chronic exposure to alcohol and to components of cigarette smoke) on TPP uptake by PAC mitochondria and delineated the molecular mechanisms involved in the observed effects (38,39). However, little is currently known about possible effect of the prevailing thiamin level on TPP uptake by PAC mitochondria.…”
mentioning
confidence: 99%